The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.1111/jam.12686
|View full text |Cite
|
Sign up to set email alerts
|

Cell-bound exopolysaccharides of Lactobacillus brevis KB290 enhance cytotoxic activity of mouse splenocytes

Abstract: We demonstrated that EPS-b produced by KB290 has a critical role in enhancing cell-mediated cytotoxic activity in mouse spleen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…It was reported that the thermal treatments increase the cell coarseness and roughness, which influence their immune-modulating properties [6,7]. In addition, heat-treated probiotics not only possess biological activities in communication with the host but also provide advantages for industrial production and consumer usage, including a longer product shelf life, easier storage, and more convenient transportation [4,6,8].…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the thermal treatments increase the cell coarseness and roughness, which influence their immune-modulating properties [6,7]. In addition, heat-treated probiotics not only possess biological activities in communication with the host but also provide advantages for industrial production and consumer usage, including a longer product shelf life, easier storage, and more convenient transportation [4,6,8].…”
Section: Introductionmentioning
confidence: 99%
“…First, this trial has a lack of information on the mechanism of KB290 + βC against influenza, as we did not measure immunological parameters such as innate immune responses or antibodies in this trial. Our previous studies have shown that live KB290 induced the production of interferon-α and immunoglobulin A in mice challenged with IAV [ 36 ] and enhanced cell-mediated cytotoxic activity in mice [ 37 ]. In addition to the immunoregulatory actions of βC [ 38 ], retinoic acid has also been reported to be associated with retinoic acid-inducible gene-I-mediated production of interferon-α and immunoglobulin A [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…This finding was in agreement with a previous report, which demonstrated that live KB290 can reduce the influence of IAV in mice [ 14 ]. In addition, both live and heat-killed KB290 have been shown to enhance cell-mediated cytotoxic activity in mice [ 66 ]. Taken together, these findings suggest that both live and heat-killed forms of KB290, could be effective in providing protection against IAV infection by possibly enhancing the function of immune cells.…”
Section: Discussionmentioning
confidence: 99%